(untitled) (Acta Scientiarum. Health Sciences, 2012)
This study described the feelings and experiences of a mother that has a child carrier of Down syndrome. This was a descriptive study with a qualitative approach of the type of case study. The subject of the study was a mother who has a daughter with Down syndrome. Data collection occurred by a semi-structured interview and non-systematic observation, from July to December 2008, during five meetings, scheduled in advance. For analysis, all the material was categorized by extensive readings and highlighting significant terms for the information encoding. Then, the questions used in the data collection were classified in sequence topics: Mother’s perception facing the diagnosis of Down Syndrome; The meaning of the concept risk baby; Explaining the Down Syndrome through religion; Mother’s perception regarding the care of the risk baby. The mother has not only difficulties to accept the child’s situation, but also in relation to to the care, justifying the need of health professionals to seek to assist these families to understand this diagnosis, minimizing their anguish, guilties and anxiety.